SIFAT WAJIB ALLAH DALAM KARYA SENI GRAFIS - Zulfadli Sayfulhak; Yofita Sandra (Serupa The Journal of Art Education, 2021)
The making of the final work of graphic art, this serigraphy technique is to visualize the mandotory nature of Allah, including calligraphy and chat serigraphy techniques using several color prints besides that it is also useful for pairing concepts and techniques for working in graphic arts. There are several stages in carrying out this final work including preparation, elaboration, synthesis, concept realization and completion stages. Thus, ten graphic art works that visualize the mandotory nature of Allah titles: first " Wujud ", second " Qidam ", third " Baqa ", fourth " Wahdaniah ", fifth " Qudarat ", sixth " Iradat ", seventh " Ilmu ", the eighth " Sama ", the ninth " Basar " and ten " Qalam ".Kata Kunci: Sifat Wajib Allah, arti , Seni Grafis.